Akselerasi Penurunan Angka Kematian Ibu Menggunakan Pendekatan Rembug melalui Strategi Segitiga Pengaman - Evie Sopacua (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
The safeguard triangle with a discussion approach can be use as a strategy in the effort to accelerate maternal mortality rate. This triangle was a recommendation of a study in Sampang and Pamekasan Districts in East Java Province through 2003-2004. The triangle consists of the village midwife, the mentor and the pregnant woman with her family in each of its corners. Through interaction of the triangle’s corners the process of discussion approach was conducted. This safeguard triangle was stated as a holistic service because the pregnant woman was involved as a subject not as an object in the discussion approach which assured woman a safe pregnancy and birth. This safeguard triangle which was conducted at the village level should be supported by the supra system in the role of stewards hipness. The discussion approach should be taken into consideration of a coordination process which was formulated to achieve a self care community for a healthy living.Keywords: safeguard triangle strategy, discussion approach, accelerate maternal mortality rate